Neurological and psychiatric presentations associated with human monkeypox virus infection: A systematic review and meta-analysis. (October 2022) - Badenoch, James B.; Conti, Isabella; Rengasamy, Emma R.; Watson, Cameron J.; Butler, Matthew; Hussain, Zain; Carter, Ben; Rooney, Alasdair G.; Zandi, Michael S.; Lewis, Glyn; David, Anthony S.; Houlihan, Catherine F.; et al.
Summary: Background: Neuropsychiatric presentations of monkeypox (MPX) infection have not been well characterised, despite evidence of nervous system involvement associated with the related smallpox infection. Methods: In this pre-registered (PROSPERO ID 336649) systematic review and meta-analysis, we searched MEDLINE, EMBASE, PsycINFO, AMED and the preprint server MedRxiv up to 31/05/2022. Any study design of humans infected with MPX that reported a neurological or psychiatric presentation was included. For eligible symptoms, we calculated a pooled prevalence using an inverse variance approach and corresponding 95% confidence intervals. The degree of variability that could be explained by between-study heterogeneity was assessed using the I 2 statistic. Risk of bias was assessed with the Newcastle Ottawa Scale and the Joanna Briggs Institute quality assessment tool. Findings: From 1705 unique studies, we extracted data on 19 eligible studies (1512 participants, 1031 with confirmed infection using CDC criteria or PCR testing) most of which were cohort studies and case series with no control groups. Study quality was generally moderate. Three clinical features were eligible for meta-analysis: seizure 2.7% (95% CI 0.7–10.2%, I 2 0%), confusion 2.4% (95% CI 1.1–5.2%, I 2 0%) and encephalitis 2.0% (95% 0.5–8.2%, I 2 55.8%). Other frequently reported symptoms included myalgia, headache and fatigue, where heterogeneity was too high for estimation of pooled prevalences, possibly as a result of differences in viral clades and study methodology. Interpretation: There is preliminary evidence for a range of neuropsychiatric presentations including severe neurological complications (encephalitis and seizure) and nonspecific neurological features (confusion, headache and myalgia). There is less evidence regarding the psychiatric presentations or sequelae of MPX. This may warrant surveillance within the current MPX outbreak, with prospective longitudinal studies evaluating the mid- to long-term sequelae of the virus. Robust methods to evaluate the potential causality of MPX with these clinical features are required. More evidence is necessary to explain heterogeneity in prevalence estimates. Funding: UKRI/MRC (MR/V03605X/1), MRC-CSF (MR/V007181/1), MRC/AMED (MR/T028750/1) and the Wellcome Trust (102186/B/13/Z) and (102186/B/13/Z) and UCLH BRC.